Possibility of Using Ballistic Missile Launchers in the Study of Shock-Compressed Substance Properties - S. I. Gerasimov; V. I. Erofeev; I. V. Zanegin; V. A. Kikeev; A. P. Kalmykov; E. G. Kosyak; P. G. Kuznetsov; N. V. Lapichev (Глобальная ядерная безопасность)
The paper describes ballistic test site equipment used for studying the physical and mechanical properties of materials exposed to intense dynamic loads. To study the properties of shock-compressed substances, explosive shock wave generators based on powerful condensed explosives are used. The methods of dispersal of the used strikers in different throwing modes with different types of guns are briefly described. The methodological development in cannon experiments on light-gas guns is given, in which the conditions of safe acceleration of the strikers in the barrels of the guns and the loading parameters of the latter which provide the required collision speeds of the striker and the target are confirmed. Numerical and experimental results of testing the selected throwing modes are presented.